2022
DOI: 10.1167/tvst.11.11.2
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Visual, Auditory, and Olfactory Functions in Community-Based Older Adults: The Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Purpose Objective examination of relationships among visual, hearing, and olfactory function may yield mechanistic insights and inform our understanding of the burden of multiple-sensory impairments. Methods This cross-sectional study capitalized on continuous measures of visual acuity (VA), contrast sensitivity, pure tone audiometry, Quick Speech-in-Noise (QuickSIN), and Sniffin’ Sticks from a subset of ARIC participants at two community sites (EyeDOC Study, 2017–2019)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…We further observed that stage 2 hypertension/(≥160/≥100) was significantly associated with a reduction in odor identification abilities. This contrasts with earlier reports who described hypertension not to be associated with odor identification ( Landis et al 2004 ; Karpa et al 2010 ; Arsiwala-Scheppach et al 2022 ). However, individuals suffering from hypertension reported subjective olfactory dysfunction significantly more often ( Roh et al 2021 ).…”
Section: Discussioncontrasting
confidence: 99%
“…We further observed that stage 2 hypertension/(≥160/≥100) was significantly associated with a reduction in odor identification abilities. This contrasts with earlier reports who described hypertension not to be associated with odor identification ( Landis et al 2004 ; Karpa et al 2010 ; Arsiwala-Scheppach et al 2022 ). However, individuals suffering from hypertension reported subjective olfactory dysfunction significantly more often ( Roh et al 2021 ).…”
Section: Discussioncontrasting
confidence: 99%